2004
DOI: 10.1007/s10681-004-3156-5
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid performance and AFLP- based genetic similarity in faba bean

Abstract: Successful prediction of heterosis and performance of F 1 -hybrids from the genetic similarity of their parents based on molecular markers has been reported in several crops and can be very helpful in hybrid breeding. The relationship between genetic similarities based on amplified fragment length polymorphism (AFLP) of 18 European faba bean lines and their hybrid performance and heterosis was investigated. Parental lines, 62 F 1 -hybrids and their F 2 -progenies were evaluated in field trials in four environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
1
4
1
1
Order By: Relevance
“…Similarly, the significant mean squares due to heterosis, variety heterosis and specific heterosis for chocolate spot disease resistance and grain yield suggested the potential of the parents for heterosis. These results confirm those obtained by Zeid et al (2004) and Alghamdi (2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, the significant mean squares due to heterosis, variety heterosis and specific heterosis for chocolate spot disease resistance and grain yield suggested the potential of the parents for heterosis. These results confirm those obtained by Zeid et al (2004) and Alghamdi (2009).…”
Section: Discussionsupporting
confidence: 92%
“…The highest heterosis for grain yield of 162.3% in this study was higher than reported in other studies, for instance 129.9% by Alghamdi (2009), 119% by (Zeid et al, 2004). The high heterosis for grain yield was detected in crosses made between the introduced inbred lines (ILB-4726, ILB-938 and BPL-710) and locally released improved varieties (NC58, Kasa, Bulga-70 and CS-20-DK).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Hybrid vigor (heterosis) is pronounced in faba bean. Heterozygous F1-hybrids exceed the yield of their homozygous parents by 40 to 70% (Zeid et al, 2004;Dieckmann and Link, 2010). Early approaches to hybrid breeding using cytoplasmic male sterility (CMS) system in faba bean trace back to David Bond in Cambridge, UK in 1957 and Pierre Berthelem in Rennes, France in 1967 (Pfeiffer et al, 1993;Link et al, 1997).…”
Section: Faba Bean Breeding Methodsmentioning
confidence: 99%
“…The AFLP markers were used to investigate the relationship between genetic similarities of 18 European faba bean lines and their hybrid performance and heterosis (Zeid et al, 2004). No previous work has been done using SSR markers to study genetic diversity in faba bean.…”
mentioning
confidence: 99%